2021
DOI: 10.3934/mbe.2021384
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic hypoxia-related genes signature on the tumor microenvironment in esophageal cancer

Abstract: <abstract> <sec><title>Background</title><p>Hypoxia is a crucial factor in the development of esophageal cancer. The relationship between hypoxia and immune status in the esophageal cancer microenvironment is becoming increasingly important in clinical practice. This study aims to clarify and investigate the possible connection between immunotherapy and hypoxia in esophageal cancer.</p> </sec> <sec><title>Methods</title><p>The Cancer Genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…However, it has a limited role in judging the accurate depth of tumor invasion into esophageal wall, and the accuracy of evaluating T staging is poor (23). PET is more sensitive than CT in the diagnosis of primary tumors, but its limited information on the depth of tumor invasion limits its role in T staging (24,25). EUS is a gastrointestinal tract examination technology that combines an endoscope and ultrasound, and it plays a vital role in the staging of esophageal cancer and determination of the origin and depth of tumors (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has a limited role in judging the accurate depth of tumor invasion into esophageal wall, and the accuracy of evaluating T staging is poor (23). PET is more sensitive than CT in the diagnosis of primary tumors, but its limited information on the depth of tumor invasion limits its role in T staging (24,25). EUS is a gastrointestinal tract examination technology that combines an endoscope and ultrasound, and it plays a vital role in the staging of esophageal cancer and determination of the origin and depth of tumors (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study focused on the prognostic role of the ir-lncRNAs with microenvironment and immune cells in ESCC is lacking, especially for ESCC with radioresistance. Identification of prognostic value of the tumor microenvironment in esophageal cancer is necessary ( Tan et al, 2021 ). In our study, we identified 11 immune genes with differential expression in the GSE 45670 cohort, and our findings further confirmed the involvement of immune alterations in the biological process of radiation resistance in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we conducted Spearman's rank correlation test to examine correlations between 150 common immunomodulators (chemokine, receptor, MHC, immunoinhibitor and immunostimulatory) as well as immune checkpoints and the expression levels of key genes, which may provide new targets for immunotherapy. Pearson coefficient was calculated to estimate correlations between genes with mutation rates over 50% and gene markers of autophagy, 16,17 ferroptosis, 18 pyroptosis and hypoxia 19,20 …”
Section: Methodsmentioning
confidence: 99%